(untitled) (Teaching and Learning Inquiry, 2021)
Summative assessments tend to be viewed as high-stakes episodes by students, directly exposing their capabilities as learners. As such, receiving feedback is likely to evoke a variety of emotions that may interact with cognitive engagement and hence the ability to learn. Our research investigated the emotions experienced by undergraduate students in relation to assessment feedback, exploring if these emotions informed their learning attitudes and behaviours. Respondents were drawn from different years of study and subject/major. A qualitative approach was adopted, using small group, semi-structured interviews and reflective diaries. Data were analysed thematically and they revealed that receiving feedback was inherently emotional for students, permeating their wider learning experience positively and negatively. Many students struggled to receive and act upon negative feedback, especially in early years, when it was often taken personally and linked to a sense of failure. Negative emotional responses tended to reduce students’ motivation, self-confidence, and self-esteem. Some students, especially in later years of study, demonstrated resilience and engagement in response to negative feedback. By contrast, positive feedback evoked intense but fleeting emotions. Positive feedback made students feel cared about, validating their self-worth and increasing their confidence, but it was not always motivational. The paper concludes with recommendations for instructors, highlighting a need to communicate feedback carefully and to develop student and staff feedback literacies.